Réponses

2014-06-03T22:08:36+02:00
2)
A = 8x - 14x
A = - 6x

B = - 14x - 29x
B = - 43x

D = x - 5 - 3x
D = - 2x - 5

E = - 15x + 1 + 7x - 4
E = - 15x + 7x + 1 - 4
E = - 8x - 3

G = 8x - 6x² - 9x + 9
G = - 6x² - x + 9

H = 17x² - 41x²
H = - 24x²

L = - 8 (4 - 6x)
L = - 32 + 48x
L = 48x - 32

M = (7 - 9b)  (4b - 6)
M = 28b - 42 - 36b² + 54b
M = - 36b² + 28b + 54b - 42
M = - 36b² + 82b - 42

N = - 7x (- 1 + 4x)
N = 7x - 28x
N = - 21x

P = (2b - 1) (8 + 5b)
P = 16b + 10b² - 8 - 5b
P = 10b² + 16b - 5b - 8
P = 10b² + 11b - 8

Tu demandes le 3) mais il n'y est pas...